ANALYSIS OF THE INFLUENCE OF UNEMPLOYMENT VARIABLES ON ECONOMIC GROWTH IN CENTRAL KALIMANTAN USING THE ERROR CORRECTION MODEL (ECM) APPROACH - Harati, Rima (Multifinance, 2024)
The objective of this study is to examine the impact of unemployment variables on Gross Regional Domestic Product (GRDP) by employing the Error Correction Model methodology. This research is conducted in Central Kalimantan from 2012 to 2023. According to the cointegration testing findings using the ECM approach, the probability of the unemployment variable is 0.3788, which is greater than the significance level of 0.05. There is a lack of cointegration or long-term balance relationship between the variables, which means that testing cannot be conducted over an extended period of time. The ECM test findings indicate that there is no significant short-term impact of the unemployment variable on GRDP in Central Kalimantan. This is supported by the probability value of the unemployment variable, which is 0.2660, above the threshold of 0.05. According to the classical assumption test, there are no signs of autocorrelation in the research model. Additionally, the Jarque Berra probability value of 0.764092 is greater than 0.05, indicating that there are no signs of heteroscedasticity. Therefore, the research model can be considered normally distributed.